Representation of Woman in the “Film Marlina: si Pembunuh dalam Empat Babak” - Retno Angraeni S; Citra Buana Halil (CENDERAWASIH: Jurnal Antropologi Papua, 2025)
In the modern era, opportunities for women and men should be equal. However, this is still far from the reality faced by women in rural areas in certain regions. Women continue to encounter various forms of gender inequality, such as stereotypes, marginalization, subordination, and the double burden. The practice of upholding justice is often marked by the inner conflict of the main character in defending her rights or fighting against injustice. "Marlina: Si Pembunuh dalam Empat Babak" is a film released in 2017 that tells the story of a rural woman named Marlina, who struggles to confront the gender injustice she experiences. According to a gender perspective, women are often represented as weak and oppressed; however, Marlina's character as a rural woman is not depicted in this way. The urgency of this research is to challenge the stereotypes about rural women as figures who are weak, oppressed, and powerless. This research employs a descriptive analysis method based on Stuart Hall's theory of deconstructive representation. The way to identify the female figures depicted in this film is by reconstructing the image of women who are identified as weak. Nevertheless, Marlina's character serves as an icon (role model) who can take action in resistance. The results of this study indicate that: First, Marlina is a female figure who attempts to break free from the conservative image often associated with rural women. Second, the message conveyed through the encoding and decoding process is that women can resist and defend their justice and self-esteem.